Organizing the Net-Wide Public Expert Evaluation Based on Collective Intelligence Technologies - B. B. Slavin; A. B. Slavin (Управленческие науки, 2018)
Public expertise is now becoming an important element of public administration within the concept of open government, allowing to develop strategic plans and programs for the state development. Without the use of network and global communications, it is impossible to organize the expertise with the participation of a large number of specialists. However, the existing network methods of public expertise are not effective, what indicates the relevance of technology study for the organization of public expertise. The purpose of the given article is to study the possibility of using collective intelligence technologies for the organization of public expertise. The research was initiated by the need to study the possibility of using public expertise in the activities of distributed situation centres, which are the basis of public administration. In this regard, a comparative analysis of public and professional expertise was carried out. Possibility of the transfer of the professional expert technology for public expertise was shown. It enables to apply the competence approach and the technologies of collective intelligence for public expertise. The substantiation of the convergence of public and professional expertise allowed to reveal the basic principles of the public expertise organization on the basis of collective intelligence technologies. Among such principles there are: the requirement of closeness of expert communities; participation of representatives of science and practice in the public expertise; competence approach; joint collaborative activities and constant mutual rating of experts. The formulated principles of the organization of public expertise are given in comparison with the use of crowdsourcing. At present, there is a certain disappointment in the use of network methods for the organization of public expertise due to the limited crowdsourcing technologies. The proposed approach to the use of collective intelligence technologies will change the attitude to public expertise as an effective and efficient management tool in the use of open government tools.